Competition, coalitions, and coordination in the global personal computer industry - Abdul Latif Haji Salleh (1997)
This dissertation argues that understanding the complexity of the global personal computer industry requires a framework that maps the relationship between distinct sectors of the industry and the power relationship among firms in a particular sector and across sectors. I use the global commodity chains framework to map the interaction between lead firms in personal computer manufacturing and its main component industries: namely, ASIC semiconductors, hard disk drives, and microprocessors. The study shows that technological change and the adoption of open standards contributed to the shift in the power structure in the industry, characterized by the diminution of power of the large computer makers and the rise of new specialized competitors residing in the different segments of the personal computer commodity chain. My empirical analysis shows that networking strategies of the lead firms in the industry were influenced by their relative power position in the industry. The study also shows that networking strategies of the U.S. start-ups were instrumental in the development of East Asia as a regional supply base for the global personal computer industry. I conclude that development policies of the less-industrialized countries in East Asia should consider the establishment of network relationships with the lead firms in the industry.